Pemodelan Pergerakan Non-Linear Dengan Memanfaatkan Fungsi Gerak Angular Pada Quadcopter - Muliyahati Sutejo; Gembong Edhi Setyawan; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Quadcopter or commonly known as unmanned aerial vehicle has four propellers on each side. The advantage of quadcopter lies in the mobility and flexibility of movement. This can be seen from the many studies developing the navigation system of motion from the quadcopter to pass through a region. The trajectory area passed by the quadcopter is not only completely straight but the crossing-shaped trajectory can also be found. This requires the quadcopter to switch directions in motion. For this reason, control of quadcopter movements is needed. In this study will build a quadcopter movement control system, so that it can shift angular direction optimally in terms of time and accuracy of quadcopter movement. By utilizing the values ​​of the angular_z, linear_x or linear_y parameters on the quadcopter and the iteration value (i) to be treated with the angular function equation. In addition, the speed of the quadcopter can be adjusted by giving a value in the linear velocity parameter with a range of 0 to 1. Based on the results of the test, angular motion can be done with the lowest linear velocity value of 0.7 and the highest is 1. For estimated motion time quadcopter in various directions obtained an average time of 0.018225 seconds. And for the accuracy of quadcopter motion, the accuracy level of success based on distance (r) taken is 99.99%.